Ixazomib or Lenalidomide combined with cyclophosphamide and dexamethasone in the treatment of elderly transplant-ineligible newly diagnosed multiple myeloma - Yan Wang; Yuan-Fang Liu; Shi-Wei Jin; Yi Tao; Wei-Ping Zhang; Jian-Lin Chen; Song-Fu Jiang; Jian-Qing Mi (Scientific Reports)
Abstract Oral-drug based regimens are useful in certain circumstances for transplant-ineligible newly diagnosed multiple myeloma (TI-NDMM), but few studies have compared Ixazomib based regimen with lenalidomide based regimen head-to-head. We carried out a prospective randomized, open, parallel group trial in patients with TI-NDMM in 3 China centers from March 2020 to December 2022. Sixty-three patients were available for final analysis, ICd (Ixazomib/cyclophosphamide/dexamethasone, n = 31) and RCd (lenalidomide/cyclophosphamide/dexamethasone, n = 32). The primary objective was to compare the two regimens by analyzing the overall response rate (ORR), safety profiles, progression-free survival (PFS) and overall survival (OS). We also explored clinical and the biological characteristics of the patients with primary drug resistance. Baseline characteristics were well balanced between ICd and RCd groups, with the median age 70 vs. 70 years; 12.9% vs. 12.5% of patients had stage III disease; 25.8% vs. 28.1% had high-risk cytogenetic abnormalities. The overall response rate (ORR) at the end of 4 cycles was 87.1% vs. 71.9% (odds ratio [OR], 1.212; 95% CI, 0.938–1.565; P = 0.213); the best ≥ VGPR rate was 41.9% vs. 31.2% (OR, 1.342; 95% CI 0.694–2.597; P = 0.439). Among high-risk cytogenetic patients, ORR was higher in the ICd group, 75% vs. 55.5% (P = 0.620), respectively. After 35 months follow-up, the median PFS were 22 and 23 months between ICd and RCd groups (P = 0.897). Median OS was not reached, estimated 3-year OS rate was 86.4% vs. 85.4% (P = 0.774). The most common adverse events of grade 3 or 4 were neutropenia (6.5% in the ICd group vs. 31.3% in the RCd group), anemia (19.4% vs. 18.8%), pneumonia (0 vs. 15.6%) and diarrhea (12.9% vs. 0). Treatment emergent adverse events (TEAEs) induced dose reduction and discontinuation were 22.6% vs. 37.5% and 3.2% vs. 6.3% in the ICd vs. RCd group, respectively. Exploration data showed that patients with t (4;14) were insensitive to initial RCd treatment. The ICd regimen showed a tendency towards improved ORR compared to RCd regimen. Both ICd and RCd regimens demonstrated less dose reduction and treatment discontinuation, suggesting their tolerability and feasibility for older individuals with TI-NDMM. Trial registration: This study was registered at Chinese Clinical Trial Register (ChiCTR). Trial registration number: ChiCTR2000029863. Date of registration: 15/02/2020.